KAZAKHSTAN-GERMAN ECONOMIC COOPERATION: CURRENT CONDITION AND PROSPECTS (International relations and international law Journal, 2016)
The article «kazakh - german cooperation: the modern stateand future prospects» holds the information about kazakh andgerman business and trade relations, german investments inkazakh economy.The article tells briefly about a year of Germany inKazakhstan which was in 2010. You also can find theinformation about kazakh - german economic forum whichtook place in Astana in July, 2010
Keywords: economic cooperation; technical cooperation